VD_FINDINFO HC / 2011 / 585 vom 31. Oktober 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, DEMEURE DU DÉBITEUR, BAIL À LOYER, RÉSILIATION IMMÉDIATE | 257d al. 1 CO, 257d al. 2 CO, 257d CO, 257 CPC (CH), 308 al. 2 CPC (CH)